America unbound : the Bush revolution in foreign policy - Daalder, Ivo H. (Brookings Institution, 2003)
George W. Bush is leading a revolution in American foreign policy. He believes that the unilateral exercise of American power is the best way to promote America's national interests. This book argues that The Bush revolution in foreign policy carries with it high risks and possibly high costs.